Crystal Structure and Hirshfeld Surface Analysis of Two 5,11-Methanobenzo[g][1,2,4]triazolo[1,5[1,3,5]oxadiazocine Derivatives - Gümüş, M.K.; Kansız, S.; Ataol, C.Y.; Dege, N.; Fritsky, I.O. (International Union of Crystallography 5 Abbey Square Chester CH1 2HU, 2019)
In the title compounds, 9-bromo-2,5-dimethyl-11,12-dihydro-5H-5,11-methanobenzo[ g][1,2,4]triazolo[1,5-c][1,3,5]oxadiazocine, C13H13BrN4O (I), and 7-methoxy-5-methyl-2-(pyridin-4-yl)-11,12-dihydro-5H-5,11-methanobenzo[g][1,2,4]triazolo[ 1,5-c][1,3,5]oxadiazocine, C18H17N5O2 (II), the triazole ring is inclined to the benzene ring by 85.15 (9) and 76.98 (5)° in compounds I and II, respectively. In II, the pyridine ring is almost coplanar with the triazole ring, having a dihedral angle of 4.19 (8)°. In the crystal of I, pairs of N-H N hydrogen bonds link the molecules to form inversion dimers with an R2 2(8) ring motif. The dimers are linked by C-H π and C-Br π interactions forming layers parallel to the bc plane. In the crystal of II, molecules are linked by N-H N and C-H O hydrogen bonds forming chains propagating along the b-axis direction. The intermolecular interactions were investigated using Hirshfeld surface analysis and two-dimensional fingerprint plots, and the molecular electrostatic potential surface was also analysed. The Hirshfeld surface analysis of I suggests that the most significant contributions to the crystal packing are H H (42.4%) and O H/H O (17.9%) contacts. For compound II, the H H (48.5%), C H/ H C (19.6%) and N H/H N (16.9%) interactions are the most important contributions. © 2019 International Union of Crystallography. All rights reserved.
Keywords: Benzoxadiazocine; Biginelli Condensation; C-Br π Interactions; C-H π Interactions; Crystal Structure; Hirshfeld Surface Analysis; Hydrogen Bonding